METHOD AND ALGORITHM FOR DETECTING NETWORK ATTACKS ON THE DISTRIBUTED DATABASE OF CORPORATE NETWORK USERS - Sadikov Sh.M. (Journal Park Publishing, 2023)
The article identifies network attacks on the distributed database of corporate network users, researches the effects of external and internal threats within the organization's information system, and analyzes effective protection measures against network attacks on the database. A partition scheme has been developed in the area section of the distributed database, and an algorithm for detecting SQL injection attacks on the distributed database has been developed.
Keywords: corporate network, distributed database, SQL injection, comparison matrix, risk, OTP.